PENERAPAN MAQĀṢID AL-SYARĪ’AH PADA MONETISASI MEDIA SOSIAL: ANALISIS PADA APLIKASI TIK TOK - Saputra, Adi; Abidin, Zainal; Azis, Fajar Rahmat; Rudin, Syafaat; Hijaz, M. Chiar (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2025)
This study examines in depth various TikTok monetization strategies from an Islamic legal perspective. It analyzes methods such as live streaming with virtual gifts, brand endorsements, affiliate marketing, and direct sales through TikTok Shop to determine whether these methods are ethically and legally permissible under Sharia. The study is qualitative with a library research approach based on primary Islamic sources (the Qur’an and Hadith) and contemporary scholarly interpretations. The analysis is guided by classical Islamic contract frameworks like ju’ālah (reward-based contract) and ijārah (service-for-hire contract), as well as the higher objectives of Islamic law (maqāsid al-sharī’ah). Findings suggest that TikTok’s monetization features have the potential to align with Islamic principles, but only with proper ethical safeguards. Income from live streaming is considered halal if the shared content is beneficial, ethical, and non-manipulative. Endorsement and sponsorship agreements can be accepted under ijārah as long as they involve halal products and honest disclosure practices. Similarly, affiliate marketing aligns with ju’ālah principles if conducted transparently and truthfully. Transactions on TikTok Shop generally meet Sharia criteria as long as they adhere to the pillars (rukun) and conditions of a valid sale (bay’), including clear pricing and the sale of lawful goods. The study emphasizes the importance of clear ethical guidelines, public education, and platform policies that uphold Islamic values while fostering digital economic innovation. It also provides theoretical and practical contributions for content creators, regulators, and academics to build a responsible and Sharia-compliant online marketplace.